VALLE CRUCIS MOBILE PERFORMANCE STAGE: A TRANSFORMATIVE RESPONSE TO A CHANGING LANDSCAPE. - EVERHART, CHAD (Journal of Appalachian Studies)
In general, buildings are comprised of numerous inactive elements and rooted to a site. With the exception of a few operable doors and windows, buildings are static. What if architecture were able to move and transform? Can a building serve multiple purposes and change appearances in an effort to adapt to its users and context? To address the vernacular architecture and fragile floodplains of the Valle Crucis community, students and faculty from Appalachian State's Building Science Program designed and built a mobile, off-grid performance stage for Valle Crucis Community Park. Since the park's former performance accommodations could no longer handle the large crowds at weekly events, a new performance stage was needed. Unfortunately, because most of the park was recently designated as a floodplain, permanent structures were not allowed unless constructed upwards of ten feet above the ground, causing acoustic, visual, and crowd interaction problems for a stage. Through extensive research and creative problem solving, a design solution was reached: build a transformable structure that serves multiple functions and can be moved based upon user needs as well as flooding.